PENERAPAN MODEL IS-DEMATEL DALAM ANALISIS KUALITAS LAYANAN RESTORAN SOLARIA DI JAKARTA TIMUR - Ronald Sukwadi (Universitas Ahmad Dahlan Indonesia, 2019)
The restaurant business has grown rapidly over time. To be able to compete with other restaurants, restaurant management must improve service quality so that customers can satisfied and loyal. This study aims to measure customer satisfaction toward the services quality of Solaria restaurant by using the integration model of the Importance-Satisfaction Model (IS) and Laboratory Decision Making and Evaluation Laboratory (DEMATEL). The IS model is used to classify service quality attributes that must be prioritized for improvement, while DEMATEL is used to understand the relationships between attributes that must be improved. The IS Â diagram shows that there are 3 attributes in the first quadrant, 4 attributes in the second quadrant, 8 attributes in the third quadrant, and 3 attributes in the fourth quadrant. The service attributes are then further analyzed in the DEMATEL model. From the results of the IS-DEMATEL model, it is obtained the priority sequence that needs to be improved by the restaurant. The main priority for repairs is a clean dining room, while the last priority is an interesting food menu.